Web-Based Information System of Sundutan Tigo Village Budget and Revenue, Mandailing Natal Regency - Limbong, Tonni; Harefa, Zecrin Damai (KAKIFIKOM : Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer, 2021)
The digital village is a community empowerment program through the use of digital technology and the internet in developing village potential, marketing and accelerating access and information services. The Sundutan Tigo Village Office is a government agency, having its address at Sundutan Tigo Village, Natal District, Mandailing Natal Regency. The Village Office has the receipt and disbursement of funds. Based on the results of the pre-survey at the research location, there are still many people who do not know how much the village fund budget is realized by their village government per year. In fact, in this case the main purpose of rolling out village funds is other than for rural development, the most important thing is how the village government empowers village communities, so that they can support national development through work carried out in villages both from an economic and other perspective. etc. For this reason, a computerized information system is needed, which is able to overcome the obstacles and problems that exist in the transparency of the village fund management.